Molecular detection and characterization of Indian isolates of Pasteurella multocida serogroup ‘D’ - DUTTA, T K; SINGH, V P; KUMAR, A A (The Indian Journal of Animal Sciences, 2011)
Five Pasteurella multocida serogroup D isolated from pig (n=4, serotype D: 1) and sheep (n=1, serotype D: 3) were tested for molecular identification and characterization. All the isolates were detected by species specific PCR (PMPCR) and ~460 bp products were obtained. RE analysis of the isolates using enzymes Hha I and Hpa II generated very clear and readable discriminatory banding profiles and 3 different RE profiles obtained out of 4 P. multocida isolates of serotype D: 1. Among the 2 enzymes used in this study, Hpa I had better discriminatory power than Hha I. Single primer based RAPD-PCR assay generated readable and distinct banding patterns between serotypes, but failed to differentiate 4 isolates of P. multocida serotype D: 1. Molecular detection using species specific PCR and characterization by molecular techniques like REA and RAPD-PCR could enable typing of P. multocida strains as a complement of classical capsular and somatic typing in preliminary characterization.Â